Infected and Stressed by Climate Variability : New Empirical Evidence from Bangladesh - Mahmud, Iffat; Raza, Wameq; Hossain, Rafi (World Bank, Washington, DC, 2021)
Bangladesh’s extreme vulnerability to the effects of climate change is well documented. Through a complex pathway, climatic conditions have already negatively impacted human health worldwide. This is likely to escalate if predicted changes in weather patterns hold. Infectious disease transmission will change in pattern and incidence for certain vector-borne diseases such as malaria and dengue, and waterborne diseases such as diarrhea and cholera. The incidence of respiratory disease will be affected by extreme temperatures that exacerbate the effects of allergens and of air pollution (World Bank 2012). If global warming progresses toward a 4°C increase scenario, a scenario presented as the worst case at the 2015 Paris Climate Change Conference of Parties, stresses on human health can overburden the systems to a point where adaptation will no longer be possible (World Bank 2012). Hence the urgent need for the public sector to be better prepared to respond to the crisis. The consequences of climate change and/or climate variability are well documented and hypothesized. The literature linking climate change or climate variability and health, however, is less so. Climate variability refers to short-term changes in the average meteorological conditions over a month, a season, or a year. Climate change, however, refers to changes in average metrological conditions and seasonal patterns over a much longer time (Mani and Wang 2014). Compared to the availability of global evidence on this topic, the evidence from Bangladesh is far more limited. Among the studies available for Bangladesh, some require further substantiation because they are mostly regional one-off studies with a range of methodological limitations. In doing so, the report responds to several key questions, summarized in this subsection. What it does not do is construct mathematical models for projecting the incidence and prevalence of infectious diseases and mental health issues based on predicted climate change patterns. Nor does it attempt to establish a causal relationship between climate change and the selected health conditions. The report uses primary data from a nationally representative sample of about 3,600 households surveyed during the monsoon and dry seasons. It links weather variables, the incidence of selected diseases, and health conditions in Bangladesh to ensure that the findings are, as much as possible, based on precise climate and health data. The recommendations, therefore, are context-specific and drawn from primary evidence.